A 9.73 GHz wide-band off-body patch antenna for biomedical applications - Niloy Goswami; Md. Abdur Rahman (Institute of Advanced Engineering and Science, 2024)
The primary goal of this study is to design a simple antenna that has a wide bandwidth and low return loss for biomedical applications. The paper shows the recommended antenna’s three-stage modeling, with the goal of assessing every important parameter while a Teflon or polytetrafluoroethylene (PTFE) polymer substrate is used. In order to better comprehend, a comparison with prior studies employing teflon and similar substrate materials is conducted for the proposed patch antenna. The analysis includes the phantom model, evaluating performance criteria such as specific absorption rate (SAR), return loss, bandwidth, and gain values relevant to biomedical applications. The antenna works at two different frequencies: 9.73 and 9.39 GHz, one in free space and another in a skin-cotton layer. The bandwidth of the antenna is 4.067 GHz in free space at the resonance frequency of 9.73 GHz, where the return loss is -62.18 dB. The performance of the proposed antenna in the field of biomedical applications, its underlying reasons, and its impacts are discussed in detail in this study.